2007
DOI: 10.3748/wjg.v13.i26.3581
|View full text |Cite
|
Sign up to set email alerts
|

Compound Danshen injection improves endotoxin-induced microcirculatory disturbance in rat mesentery

Abstract: stained with Monastral blue B, rolling and adhesion of leukocytes, production of oxygen radical in venular wall, albumin efflux and enhanced mast cell degranulation in vivo , all of which, except for the leukocyte rolling, were attenuated by the treatment with compound Danshen injection. Experiments performed in vitro further revealed that the expression of CD11b/CD18 and the production of oxygen free radical in neutrophils, and the expression of ICAM-1 in HUVECs were increased by exposure to LPS, and they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…In the present study, we provide compelling experimental evidence supporting the efficacy of Rb1 therapy for mesentery albumin leakage induced by LPS. Previous studies in our laboratory have demonstrated that LPS intravenous infusion at a concentration of 5 mg/kg effectively evoked hyperpermeability in microvessels (13,44). Consistent with our previous studies, with the use of inverted intravital microscopy, the present study revealed that FITC-labeled albumin leaked markedly out of mesenteric microvessel 30 min after LPS infusion and increased linearly with time.…”
Section: G296supporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we provide compelling experimental evidence supporting the efficacy of Rb1 therapy for mesentery albumin leakage induced by LPS. Previous studies in our laboratory have demonstrated that LPS intravenous infusion at a concentration of 5 mg/kg effectively evoked hyperpermeability in microvessels (13,44). Consistent with our previous studies, with the use of inverted intravital microscopy, the present study revealed that FITC-labeled albumin leaked markedly out of mesenteric microvessel 30 min after LPS infusion and increased linearly with time.…”
Section: G296supporting
confidence: 92%
“…After being anesthetized with urethane (2 g/kg body wt im), the left femoral vein and left jugular vein of the rat were cannulated. In the LPS group, LPS solution in saline was infused (5 mg·kg Ϫ1 ·h Ϫ1 ) for 90 min via the left femoral vein, as previously described (13,44). The vehicle, instead of LPS solution, was administrated in Sham and Rb1 alone (Rb1) groups.…”
Section: Methodsmentioning
confidence: 99%
“…[17] It mainly contains water-soluble and bioactive phenolic acids, such as propanoid acid (PA), protocatechualdehyde (PHA), salvianolic acid B (SAB), salvianolic acid A (SAA), and rosmarinic acid (RA). [18] Although some researchers have indicated that Danshen injection possess low acute and sub-chronic toxicity,[19] more and more ADR cases induced by it are reported in the recent years. [20]…”
Section: Introductionmentioning
confidence: 99%
“…Chemical compounds from Salvia miltiorrhiza can be classified into two major categories: hydrophilic compounds and lipophilic diterpenoid quinines (LDQ). Both hydrophilic and lipophilic compounds of Danshen have multiple pharmacological activities, such as improving the microcirculatory disturbance, protecting against cardiotoxicity induced by doxorubicin, inhibiting the proliferation of vascular smooth muscle cells, anti-inflammatory, anti-platelet, anti-oxidant and vasorelaxation (Seon-il et al, 2003;Wang et al, 2005;Han et al, 2007;Jiang et al, 2009;Wu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%